Biocementation of soil by calcite/aragonite precipitation using Pseudomonas azotoformans and Citrobacter freundii derived enzymes. Issue 31 (4th June 2019) - Abdel-Aleem, Heba; Dishisha, Tarek; Saafan, Amal; AbouKhadra, Abduallah A.; Gaber, Yasser
Abstract : Microbial geotechnology is the use of microorganisms and/or their derivatives to alter engineering properties of soil for improving its stability, strength and stiffness. Abstract : Microbial geotechnology is the use of microorganisms and/or their derivatives to alter engineering properties of soil for improving its stability, strength and stiffness. Ureases hydrolyze urea in the soil leading to CaCO3 precipitation, which binds soil particles together (biocementation). In the present study, nine Egyptian soils were screened for urease-producing bacteria, 15 isolates were obtained, and optimum urease producers were identified. Growth kinetics were measured at different pH values and in the presence of molasses as the sole carbon source. Citrobacter freundii and Pseudomonas azotoformans showed the highest extracellular urease activities of 45.5 ± 3.4 and 54.9 ± 3.5 U ml −1, respectively. Cell-free supernatants of these isolates mediated the precipitation of CaCO3 from the cementation solution (urea and CaCl2 ). The X-ray diffraction (XRD) of the precipitates revealed the formation of calcite and aragonite crystal forms. Sandy soil treated with the supernatants and evaluated by modified proctor and California bearing ratio (CBR) tests had significantly higher ( P < 0.05) soil strength (CBR = ∼40% versus 30% for untreated soil). Scanning electron microscopy showed the CaCO3 precipitation resulting in reduction of the gaps between soil particles, hence confirming the biocementation phenomenon which is responsible for soil stabilization and the desired repairing effect on cracks. The use of urease-containing cell-free supernatant rather than the whole microorganism in biocementation lowers the risks of spreading pathogens to the environment and altering the microbial diversity at the application area.